Experience of Healthy Adult Women with the Receptive Music Therapy Using Body-Monochords – Qualitative Phenomenological Study - Kantor, Jiri; Hamáčková, Michaela (Social Welfare: Interdisciplinary Approach, 2024)
Resonance chair/harmonisation recliner are prototypes of body-monochords that were developed in the Czech Republic. These instruments are therapeutically used in music therapy practice, healthcare institutions and by people with disabilities. The aim of this study was to understand how people experience this intervention in the context of private music therapy practice. The design of this qualitative study was based on phenomenology. Six healthy women on maternity leave reflected their experience through semistructured interviews before and after therapeutic session with resonance chair/harmonisation recliner. Interpretative phenomenological analysis was used to identify 12 themes describing the course of these sessions. The women experienced changes on physical, cognitive, and emotional levels related to relaxation and muscles relieve, calming of mind, different experience with feeling of vibrations, vivid imaginations, or changes in body perception. Intervention on resonance chair/harmonisation recliner offered positive experience to the participants and provided them with a space for self-care and rest. No serious adverse events were reported by the participants during or after the intervention. The intervention using resonance chair/harmonisation recliner was highly valued by our participants and has a meaningful usage in private music therapy practice. Future researchers may explore long-term experience of participants and identify other populations that may have specific benefit from this intervention.